HUBUNGAN PERILAKU KONSUMTIF DENGAN HARGA DIRI PADA REMAJA PUTRI DI SMA NEGERI 10 YOGYAKARTA - Wahyu Rochdiat M (Universitas Respati Yogyakarta, 2020)
Background: Consumptive behavior in girl teenagers is affected by internal and external factors. One of the internal factors that affect teenagers to behave consumptively is self-esteem. Objective: To analyze the relationship of consumptive behavior with self esteem of girl teenagers in SMA Negeri 10 Yogyakarta. Methods: This research used quantitative research method, with the subject of research as many 91 students of class X SMA Negeri 10 Yogyakarta selected with purposive sampling from 118 students. Result: The result of this research shows that the majority of respondents are consumptive behavior in the medium category as much as 54 respondents (59.3%) and self-esteem in high category as much 65 respondent (71.4%). Bivariate test using Kendall-Tau found that coefficient value (r) = 0.637 and p-value = 0.00 (p <0.05).Conclusion: This research shows a positive and significant correlation between consumptive behavior with self esteem in students of class X SMA Negeri 10 Yogyakarta.